Flexibility along the neck of the Neogene terror bird Andalgalornis steulleti (Aves, Phorusrhacidae) - Tambussi, Claudia Patricia (2012)
Background: Andalgalornis steulleti from the upper Miocene-lower Pliocene (≈6 million years ago) of Argentina is a medium-sized patagornithine phorusrhacid. It was a member of the predominantly South American radiation of 'terror birds' (Phorusrhacidae) that were apex predators throughout much of the Cenozoic. A previous biomechanical study suggests that the skull would be prepared to make sudden movements in the sagittal plane to subdue prey. Methodology/Principal Findings: We analyze the flexion patterns of the neck of Andalgalornis based on the neck vertebrae morphology and biometrics. The transitional cervical vertebrae 5th and 9th clearly separate regions 1-2 and 2-3 respectively. Bifurcate neural spines are developed in the cervical vertebrae 7th to 12th suggesting the presence of a very intricate ligamentary system and of a very well developed epaxial musculature. The presence of the lig. elasticum interespinale is inferred. High neural spines of R3 suggest that this region concentrates the major stresses during downstrokes. Conclusions/Significance: The musculoskeletal system of Andalgalornis seems to be prepared (1) to support a particularly big head during normal stance, and (2) to help the neck (and the head) rising after the maximum ventroflexion during a strike. The study herein is the first interpretation of the potential performance of the neck of Andalgalornis in its entirety and we considered this an important starting point to understand and reconstruct the flexion pattern of other phorusrhacids from which the neck is unknown.